VaR when volatility is changing - Sheedy, Elizabeth (Henry Stewart Talks, 2008)
What can we learn from problems with VaR models?, Common patterns in volatility (the clustering effect), Forecasting volatility using GARCH, Implications for VaR, stress testing and capital requirements
Archived at 2022/04/04